ULTRASTRUCTURAL CHARACTERISTICS OF THE RAT GASTRIC FUNDIC WALL AFTER THE IMPACT OF THE COMPLEX OF FOOD ADDITIVES - Yachmin А.І.; Yeroshenko, G.A.; Shevchenko, K.V.; Hapon, S.V.; Vatsenko, A.V.; Ulanovska-Tsyba, N.A.; Sokolenko, V.M. (World of Medicine and Biology, 2022)
The main submicroscopic changes in the gastric wall of rats after exposure to monosodium glutamate, sodium nitrite and Ponceau 4R were determined. It was found that the effect of a complex of food additives on the mucous membrane of the fundus of the stomach of rats led to a violation of secretion and secretion, which at the ultrastructural level was manifested by violations of architecture and electron density of secretory granules in major exocrinocytes, cervical mucocytes and superficial epithelium. The impact of the complex of food additives on the mucous membrane of the rat gastric fundus is manifested primarily by dystrophic changes in superficial scrobiculus exocrinocytes, which are in direct contact with exogenous factors, as well as in the exocrinocytes of gastric glands; disorders of microcirculation are also noted.